2020
DOI: 10.1093/humrep/deaa020
|View full text |Cite
|
Sign up to set email alerts
|

Non-classic cytochrome P450 oxidoreductase deficiency strongly linked with menstrual cycle disorders and female infertility as primary manifestations

Abstract: STUDY QUESTION Can cytochrome P450 oxidoreductase deficiency (PORD) be revealed in adult women with menstrual disorders and/or infertility? SUMMARY ANSWER PORD was biologically and genetically confirmed in five adult women with chronically elevated serum progesterone (P) who were referred for oligo-/amenorrhea and/or infertility. WHAT IS KNOWN ALREADY PORD is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(53 citation statements)
references
References 44 publications
1
52
0
Order By: Relevance
“…It is an autosomal recessive disease typically diagnosed in neonates and children with ambiguous genitalia and/or skeletal abnormalities. It is responsible for the decreased activity of several P450 enzymes, including CYP21A2, CYP17A1, and CYP19A1, that are involved in adrenal and/or gonadal steroidogenesis [148]. In a study by Yatsuga et al [147] on the clinical characteristics of PORD in Japan, it is shown that in many cases, PORD can be diagnosed at <3 months of age.…”
Section: Congenital Adrenal Hyperplasia In Female/adrenogenital Syndrmentioning
confidence: 99%
“…It is an autosomal recessive disease typically diagnosed in neonates and children with ambiguous genitalia and/or skeletal abnormalities. It is responsible for the decreased activity of several P450 enzymes, including CYP21A2, CYP17A1, and CYP19A1, that are involved in adrenal and/or gonadal steroidogenesis [148]. In a study by Yatsuga et al [147] on the clinical characteristics of PORD in Japan, it is shown that in many cases, PORD can be diagnosed at <3 months of age.…”
Section: Congenital Adrenal Hyperplasia In Female/adrenogenital Syndrmentioning
confidence: 99%
“…Several phenotypic features were very common in PORD women but occurred across a range of mutations, including of high serum concentrations of P (100%), pregnenolone (100%), 17OHP (96%), corticosterone (83%) and deoxycorticosterone (DOC)(70%), DSD(78%), ovarian cysts(39%), skeletal malformations(84%), and adrenal insu ciency(78%) with most of mild cases [6]. For lateonset PORD primary amenorrhea/oligomenorrhea or infertility could be the main clinical manifestation [7,8,9], but little is known about the optimal way to investigate and treat patients with adult-onset PORD. Our case presented with features of high P and 17OHP, primary amenorrhea, ovarian cyst, minor skeletal malformation and no obvious sign of adrenal insu ciency.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent published paper from France, PORD was biologically and genetically con rmed in ve adult women with chronically elevated serum P who were referred for oligo-/amenorrhea and/or infertility, and two of these ve PORD women were reported to obtain successful live births by assisted reproductive treatment [9]. However comparing with our case, the two patients had milder clinical phenotypes with oligomenorrhea and infertility, and two different compound heterozygous mutations of c.1249-1G > C/ c.1324C > T and c.1825C > T/ c.1859G > C in POR gene [9]. Our case provided additional information of effective infertility treatment in PORD women with different ethnicity, clinical phenotype and POR gene mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with PORD occur mostly in neonates and children, and have a range of skeletal malformations, glucocorticoid de ciency and disorders of sexual development (DSD) [7]. Although one pair of POR mutations can impair all microsomal cytochrome P450 enzymes, each enzyme is affected to a different extent (depending on the locations of the POR gene mutations), resulting in high clinical variability of PORD, such as it has been reported that young girls or women only had incomplete pubertal development, primary amenorrhea, oligomenorrhea or infertility with or without skeletal malformations [2,22,24]. The clinical course of PORD in adulthood and the long-term consequence for female fertility remain unknown.…”
Section: Introductionmentioning
confidence: 99%